2005
DOI: 10.1111/j.1469-0691.2005.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Acinetobacter baumannii and other Acinetobacter spp. in faecal samples from non-hospitalised individuals

Abstract: In total, 226 individuals from the community were investigated for faecal carriage of Acinetobacter spp. by broth enrichment culture, followed by growth on blood agar and/or Leeds Acinetobacter Medium (LAM). Acinetobacter baumannii was isolated on both LAM and blood agar from one of 100 specimens in the UK and one of 126 specimens in The Netherlands. The predominant species were Acinetobactor johnsonii and genomic sp. 11, which were cultured from 22 and five specimens, respectively. A. baumannii did not seem t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 24 publications
2
48
2
Order By: Relevance
“…In patients hospitalized on a regular ward, the carriage rate of Acinetobacter species was even higher, at 75% (495). Dijkshoorn et al studied fecal carriage of Acinetobacter and found a carrier rate of 25% among healthy individuals, with A. johnsonii and Acinetobacter genomic species 11 predominating (126). In contrast, A. baumannii, the most important nosocomial Acinetobacter species, was found only rarely on human skin (0.5% and 3% in references 31 and 495, respectively) and in human feces (0.8%) (126), and Acinetobacter genomic species 13TU was not found at all (31,126,495).…”
Section: Natural Habitatsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients hospitalized on a regular ward, the carriage rate of Acinetobacter species was even higher, at 75% (495). Dijkshoorn et al studied fecal carriage of Acinetobacter and found a carrier rate of 25% among healthy individuals, with A. johnsonii and Acinetobacter genomic species 11 predominating (126). In contrast, A. baumannii, the most important nosocomial Acinetobacter species, was found only rarely on human skin (0.5% and 3% in references 31 and 495, respectively) and in human feces (0.8%) (126), and Acinetobacter genomic species 13TU was not found at all (31,126,495).…”
Section: Natural Habitatsmentioning
confidence: 99%
“…Dijkshoorn et al studied fecal carriage of Acinetobacter and found a carrier rate of 25% among healthy individuals, with A. johnsonii and Acinetobacter genomic species 11 predominating (126). In contrast, A. baumannii, the most important nosocomial Acinetobacter species, was found only rarely on human skin (0.5% and 3% in references 31 and 495, respectively) and in human feces (0.8%) (126), and Acinetobacter genomic species 13TU was not found at all (31,126,495). More recently, Griffith et al investigated the nares of healthy U.S. soldiers and did not find acinetobacters at all, but they did not use enrichment culture to increase the recovery rate (211).…”
Section: Natural Habitatsmentioning
confidence: 99%
“…In the present study, we validated the PRBS method, which consists of PCR and sequencing of a Table S1, available with the online version of this paper. The LUMC strains (with designations LUH or RUH) comprised mostly human clinical isolates, many of which had been used in previous studies (Bouvet & Jeanjean, 1989;Dijkshoorn et al, 2005;Nemec et al, 2007;Tjernberg & Ursing, 1989). The strains identified by well-established identification methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The fecal carriage rate of Acinetobacter spp. were detected up to 25% by Dijkshoorn et al and the predominant species were Acinetobacter johnsonii and Acinetobacter genomic species 11 [15]. Chu et al found 53% of medical students and new nurses to be colonized with Acinetobacters in summer versus 32% in winter [16].…”
Section: Source and Occurrencementioning
confidence: 99%